Pendampingan Masyarakat Tentang Tanaman Obat Dalam Mencegah Diabetes Melitus Di Kelurahan Kampung Baru Kecamatan Baranti - Izza, Nurril Cholifatul; Yusraa, Yusraa; Marpaung, Mauritz Pandapotan; Makualaina, Fenska Narly; Rambu, Sitti Herliyanti; Artama, Syaputra; Lestari, Ima Mustika Tri (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Diabetes mellitus has become a serious and chronic metabolic disorder resulting from a complex interaction of genetic and environmental factors. This disease has become one of the most common metabolic disorders and continues to increase to alarming levels throughout the world. One effort to prevent diabetes mellitus that is safe and affordable is to use medicinal plants. The aim of this community service is to increase public knowledge about the importance of using TOGA for the treatment of diabetes mellitus. The method used in this activity is a lecture method followed by a question and answer discussion. Participants in the activity were from the Kampung Baru Village community where the participants' education level was at high school level. From this activity, it was discovered that before the material was delivered, 45% of participants had knowledge about medicinal plants that can prevent diabetes mellitus and after the material was delivered it was 97%. The conclusion of this activity is that participants' knowledge increased regarding what medicinal plants can be used to prevent diabetes and how to use them.